Geographic variation in the skull morphology of the lesser grison (Galictis cuja: Carnivora, Mustelidae) from two Brazilian ecoregions - Migliorini,Raissa Prior; Fornel,Rodrigo; Kasper,Carlos Benhur (PeerJ, 2020)
Background The lesser grison (Galictis cuja) is one of the least known carnivores in the Neotropical region. Its wide geographical occurrence and range of habitats could lead to morphological variations along its distribution. So, this study aimed to investigate the variation in skull shape and size of this species, by testing the existence of ecotypes adapted to their respective environments (Uruguayan savanna and Atlantic Forest), as well as its relationship with selected abiotic variables. Methods The skulls of 52 museum specimens were photographed in the ventral, dorsal, and lateral views, and were analyzed using geometric morphometric techniques. Results We found sexual size dimorphism, with males being larger than females. The shape variation between sexes, as well as between ecoregions, is mostly explained by the effect of allometry. The specimens from Uruguayan savanna are larger than the ones from the Atlantic Forest. Size variation was also significantly correlated to latitude, temperature and precipitation patterns. No correlation between skull shape with geographical distance was detected. Discussion Morphometric measurements and diet data of lesser grison in regions from higher latitudes than our sampling show a tendency to heavier individuals, and the consumption of bigger prey compared to Uruguayan savanna. The results indicated the smaller specimens associated to low variability in annual temperature, congruent to Atlantic Forest region. An explanation for observed variation may be related to the “resource rule” but, due the minimal natural history information regards this species, we can just speculate about this.
Keywords: Geometric morphometrics; Intraspecific variation; Sexual dimorphism; Uruguayan savanna; Atlantic Forest